Exploring University Students’ Perceptions and Attitudes Toward Podcast in English Learning - Hendrawan, Shafira Zinedhina Hauda Sari; Rachman, Dzul; Khusnul Khatimah, Khusnul Khatimah (JELITA, 2025)
This research aimed to (i) explore English Language Education students’ perceptions of podcasts as a tool for enhancing English language learning; (ii) examine the impact of podcasts on students’ motivation to learn English; and (iii) identify the challenges faced by students when using podcasts for learning. This qualitative research used a constructivism approach and applied thematic coding in data analysis. The research participants were ten English education students at Universitas Muhammadiyah Kalimantan Timur, selected through purposive sampling. Data were collected through semi-structured interviews. The findings revealed that most students perceived podcasts as flexible, enjoyable, and useful for improving listening and speaking skills. Podcasts also positively influenced students’ motivation and confidence. However, challenges such as fast-paced speech, native accents, lack of interactivity, and technical issues were noted. Overall, podcasts are effective as supplementary tools in language learning, particularly in enhancing listening and speaking competence.